Autoimmune Dermatitis associated with Endogenous Progesterone Hypersensitivity: a case report - Nogueira Rodrigues, Andrea Railla; Matos Oliveira, Paula (Brazilian Journal of Case Reports, 2022)
Progesterone hypersensitivity (HP), also known as autoimmune progesterone dermatitis, is a rare condition with dermatological or systemic manifestations associated with progestogen, whether endogenous or synthetic. Its symptoms appear in the luteal phase and precede the menstrual flow a few days and may extend after the end of menstruation. The pathophysiology is still uncertain, and some hypotheses have been published in an attempt to explain the cases associated with both endogenous and synthetic progesterone. The diagnosis is clinical, but some tests are described in an attempt to help confirm the diagnosis. Hormonal contraceptives, antihistamines, corticosteroids and even bilateral oophorectomy are therapeutic options described. This paper describes the case report of a 28-year-old woman, nulliparous, with symptoms of macules and papules that started three days before the menstrual flow, without external triggering factor. After using a combined oral contraceptive and antihistamine, she progressed with significant clinical improvement. In view of these points and due to the scarcity of evidence on hypersensitivity to progesterone, it is essential to produce more studies on the clinical presentation, triggering factors and therapeutic possibilities for a better diagnostic elucidation and treatments of these patients.